Theological Discourse in the Formation of the Literary Tale: How Worldview came to Dominate Narrative - Matiychak, Aliona; Chervinska, Olha; Basniak, Tetiana; Nikoriak, Natalia; Tychinina, Alyona (Interlitteraria, 2022)
This study is motivated by new perspectives in expending the boundaries of multidisciplinary research. The article examines the discourse of the literary tale in the regard of its theological specificity as worldview dominants of narrative. The most significant samples of German, Russian, Ukrainian, Polish, and Romanian tales are analysed, taking into consideration the national ethos. The genre specificity is explored in the historical and cultural context with the emphasis placed on its difference from the folktale. The previous research indicates that receptive poetics of literary tales of this type is not sufficiently studied. The paper aims to examine the specificity of the literary tale genre in the ethno-national historical context, considering the main aspects of the Christian-religious ethos of the 19th century. Our methodology included integrative multidisciplinary approach that combines principles of historical poetics, hermeneutics, receptive poetics and classical methods of folkloristics in the light of transitivity theory. The findings support that reception peculiarities of Christian tale poetics are predominantly revealed according to plot evolvement, personosphere, chronotope, Christian tokens, divine symbols and paradigms. Attention was paid both to the encoded religious intentions of literary tales (this requires receptive decoding of allusions) and to the transparently expressed appeals to God with the emphasis on Christian hermeneutic instruction. Overall, the distinction of the genres of Christian fairytale, Christmas tale and Christian fantasy appeared to be the most productive. We conclude that the genre matrix of the fairytale remains open to various modifications, and consequently, fairytale narrative structures with Christian motifs actuate other genre forms. It is emphasized that the reception of the theological discourse of a literary tale depends on the readers’ psycholinguistic competencies, the peculiarities of their religious identity.
Keywords: Literary Tale, Theological Discourse, reception